Integrating work-based learning into open distance learning in higher education – examining the prospects in a developing context from a student perspective. Issue 1 (2nd January 2019) - Abukari, Abdulai; Ahmed, Bawa Kuyini
ABSTRACT: There is growing demand for access to higher education (HE) in developing countries in the midst of limited resources. Open and distance education (ODL) has become a pivotal component of HE; many developing countries have developed their own models of ODL that are consistent with their national contexts. Research has shown that many developing countries are using ODL as one of the means to boost participation rates and to reduce cost in HE delivery. However, to what extent can this alternative be used strategically beyond the access argument to make HE more pragmatic, especially strongly linked to the workplace needs of students who are mostly in employment whilst maintaining the criticality required at such a level? Based on students' perspective in Ghana, this paper uses the concept of Work Based Learning as one of the evolving 'models' of HE delivery to explore how it could be relevant in making ODL in a developing context more pragmatic and tailored towards students' needs at the workplace.